(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Paclitaxel-loaded alginate-chitosan complex microcapsules were successfully prepared by the high-voltage electrostatic technique. The effect of paclitaxel concentration and drug-loading methods on drug loading of alginate-chitosan microcapsules, and the effect of methanol concentration, chitosan concentration and chitosan molecular weight on encapsulation efficiency were investigated. Experimental results showed that calcium alginate beads had a good degree of sphericity and a uniform size of 299.8 ± 3.6 μm. After encapsulation with chitosan membrane followed by freeze drying, microcapsules shrunk and collapsed with a mean particle size of about 60.0 μm. Drug loading results showed that as paclitaxel concentration increased from 2 mg/mL to 8 mg/mL, drug loading of microcapsules was increased from 1.95% to 11.16%. Microcapsules with dynamical paclitaxel-loading at 30 °C had the highest drug loading, followed by those with statical paclitaxel-loading at 4 °C and 37 °C. Encapsulation efficiency results showed that microcapsules washed with 0.5% (v/v) methanol had the highest encapsulation efficiency of 2.85%. The encapsulation efficiency was decreased with the increase of chitosan concentration, while it firstly decreased and then increased with the increase of molecular weight of chitosan. These results provide primary information about drug loading and encapsulation efficiency properties of paclitaxel-loaded alginate-chitosan microcapsules as a novel drug carrier.